Adipose tissue monomethyl branched‐chain fatty acids and insulin sensitivity: Effects of obesity and weight loss. (18th October 2014) - Su, Xiong; Magkos, Faidon; Zhou, Dequan; Eagon, J. Christopher; Fabbrini, Elisa; Okunade, Adewole L.; Klein, Samuel
<x xml:space="preserve">Abstract</x> Objectives An increase in circulating branched‐chain amino acids (BCAA) is associated with insulin resistance. Adipose tissue is a potentially important site for BCAA metabolism. It was evaluated whether monomethyl branched‐chain fatty acids (mmBCFA) in adipose tissue, which are likely derived from BCAA catabolism, are associated with insulin sensitivity. Methods Insulin‐stimulated glucose disposal was determined by using the hyperinsulinemic‐euglycemic clamp procedure with stable isotope glucose tracer infusion in nine lean and nine obese subjects, and in a separate group of nine obese subjects before and 1 year after Roux‐en‐Y gastric bypass (RYGB) surgery (38% weight loss). Adipose tissue mmBCFA content was measured in tissue biopsies taken in the basal state. Results Total adipose tissue mmBCFA content was ∼30% lower in obese than lean subjects (P = 0.02) and increased by ∼65% after weight loss in the RYGB group (P = 0.01). Adipose tissue mmBCFA content correlated positively with skeletal muscle insulin sensitivity (R2 = 35%, P = 0.01, n = 18). Conclusions These results demonstrate a novel association between adipose tissue mmBCFA content and obesity‐related insulin resistance. Additional studies are needed to determine whether the association between adipose tissue mmBCFA and muscle insulin sensitivity is causal or a simple association.